PEMBELAJARAN MUFRADĀT PADA ANAK TINGKAT PEMULA DI PONDOK PESANTREN MIFTAHUL ULŪM PANYEPPEN - Rohman, Taufikur; Hanifah, Umi; Abdullah, Moh; Ilzam, Ahmadur; Sulfiatin, Sulfiatin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This study employs a qualitative descriptive approach, utilizing a case study of early childhood learners at the Miftahul Ulum Panyeppen Islamic Boarding School. The research findings indicate that students who have studied the Al-Miftah Lil Ulum method and the Fathul Qorib book exhibit several advantages in vocabulary learning within the context of Arabic language education. Some of these advantages are as follows: 1. Increased responsiveness in memorizing Arabic vocabulary: Children are more adept at memorizing Arabic vocabulary as they are already familiar with it through the Fathul Qorib learning process. 2. Ease in constructing sentences with memorized vocabulary: They find it easier to construct sentences using the vocabulary they have memorized, as they have mastered the principles of Nahwu (Arabic syntax) in the Al-Miftah Lil-Ulum instruction. 3. Ability to expand memorized vocabulary: They can develop the vocabulary they have memorized because they have also mastered Sarraf (Arabic morphology) in the Al-Miftah Lil-Ulum instruction. The benefits of this research are expected to contribute to both practical and conceptual understandings of Arabic language instruction for beginner-level children in Islamic boarding schools. The implications extend to the development of more effective curricula and teaching strategies within the boarding school environment. These findings also provide a foundation for further research in Arabic language education and the success of the Al-Miftah Lil Ulum method in enhancing the Arabic language proficiency of beginner-level children.